Diagnóstico microbiológico, imunoenzimático e molecular e perfil de genes associados à virulência de Campylobacter - Quetz, Josiane da Silva (2013)
Campylobacter sp. is an important cause of food-borne gastroenteritis with high incidence in children living in developing countries. However, the specific diagnosis of its etiology remains as a challenge, since conventional diagnosis by culture is now challenged by molecular and immunoenzymatic methods, which have greater sensitivity. We postulate that the knowledge of its virulence and specific diagnosis may assist in identifying and potentially controling campylobacteriosis in childhood. We determined the etiology of Campylobacter sp. associated diarrhea, in a cross-sectional study of diarrhea in children aged 0-36 months from the urban area of Fortaleza, Ceará, Brazil, who required emergency medical care because of diarrheal disease. After ethical approval of the study, a questionnaire was applied to describe the clinical conditions presented by each child at the time of admission. DNA was extracted directly from fecal samples collected from 226 children. For the determination of the etiologic agent we used molecular diagnostics (PCR and RT-PCR) and diagnostic immunoassay (ELISA), besides the detection of virulence associated genes of C. jejuni (PCR). Campylobacter sp. was found in 8.9% (20/225) of the samples by conventional microbiological diagnosis. C. jejuni and C. coli were detected in 19.5% (44/226) and 1.3% (3/226) of the diarrheic samples, respectively. The diagnostic RT-PCR and ELISA reached 26.7% (60/225) and 37.9% (58/153) of positivity, respectively. When considering the combination of diagnostic (positive in microbiological diagnosis or immunoassay and at least one of the molecular tests) the prevalence was 16.4% (37/226). The agreement between the tests used for diagnosis was moderate to regular, according to Kappa index. The presence of C. jejuni´s virulence-associated genes that encode proteins related to the pathogenesis of micro-organism were detected in the following proportions of C. jejuni-positive DNA samples: flaA, 79.5% (35/44); racR, 97.7% (43/44) and dnaJ, 88.6% (39/44) – related to bacterial adhesion and colonization; ciaB, 97.7 % (43/44); pldA, 45.4% (20/44) and pVir 0% (0/44) – related to invasion, and cdtABC in 95.4% (42/44) of samples related to citoletal distending toxin (CDT). Specific signs and symptoms such as blood in the stool, vomiting, fever and/or abdominal pain, although quite frequent, were not associated with the detection of C. jejuni. The distribution profile of C. jejuni´s virulence genes was not correlated with the clinical presentation of the disease, even when this profile was categorized according to the function of the proteins encoded by the genes, which leads us to believe that other factors, perhaps related to host susceptibility, may be more important than genetic variability of the microorganism. We conclude that Campylobacter sp. was detected in a significant percentage of the children 0-36 months with diarrhea, especially when the diagnostic methods were used in combination. In general, the virulence genes were detected in a high proportion of C. jejuni-positive samples, although the invasion-related genes have been found less frequently. Our data corroborates findings from other groups on the need to revise the diagnostic for Campylobacter sp. towards the inclusion of more sensitive and species-specific methods, as well as search for extra markers for intestinal inflammation and predictors of negative culture.